Disaster Preparedness Among University of Indonesia’s Public Health Student: A Campus Study - Ridha Syalli Adha; Fatma Lestari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: This study examines the disaster resilience of students from the Faculty of Public Health at the University of Indonesia. It employs a quantitative descriptive cross-sectional design with a sample size of 417 individuals.Objective: The objective of this study is to assess the level of disaster resilience among students of the Faculty of Public Health at the University of Indonesia and identify areas for improvement.Method: A quantitative descriptive cross-sectional study was conducted among 417 students from the Faculty of Public Health at the University of Indonesia. Data were collected using a structured questionnaire focusing on various aspects of disaster resilience, including awareness of disaster potential, preparedness, education sources, insurance ownership, disaster response, and knowledge of nearby clinics/hospitals.Result: The findings indicate that overall, the level of disaster resilience among students of the Faculty of Public Health at the University of Indonesia is satisfactory. However, there is room for improvement in certain areas such as disaster preparedness, knowledge of early warning systems, training or simulation, and readiness for disasters.Conclusion: In conclusion, while students demonstrate a commendable level of disaster resilience, there is a need for enhancement in specific areas. This could include improving disaster preparedness, increasing knowledge of early warning systems, providing training or simulation exercises, and enhancing overall disaster readiness.